Eugenic Sterilization in 20Th Century Georgia: From Progressive Utilitarianism to Individual Rights - Smith, Stephen Michael (2010)
The science of human breeding, known as eugenics, flourished in America in the first half of the 20th century. The movement's chief proponents included wealthy philanthropists, politicians, doctors, and young middle-class reformers. Sterilization for the purposes of removing defective genes from society was a critical part of the eugenics movement. Progressive reformers used eugenic doctrines combined with utilitarian political philosophy to divest individuals of the natural right to procreation. Involuntary sterilization legislation spread throughout the United States after the 1927 Buck v. Bell Supreme Court decision that gave judicial approval to involuntary sterilization, regardless of due process and equal protection arguments to the contrary. It was in this legal environment that Georgia adopted sterilization legislation as a cost-saving measure. When progressive politicians assumed control of the governorship and legislature in 1937, sterilization legislation passed with little meaningful objection. Over 3,000 involuntary sterilizations were performed in Georgia. Newly revealed documents from the Georgia Department of Archives and History show that social deference to scientific expertise, bolstered by legal coercion, poverty, or lack of education, was a major reason for the eugenics movement in Georgia. Dr. Thomas G. Peacock, in his dual role as head of the State Board of Eugenics and the superintendent of the asylum in Milledgeville, oversaw the majority of sterilizations in Georgia. He was undeterred by the revelation of Nazi eugenic practices after World War II. Sterilizations in Georgia went into decline once a new superintendent was appointed at Milledgeville who did not explicitly endorse eugenic theory. Since 1970 sterilization law in Georgia has been narrowed in scope to insure due process and equal protection for any mental incompetent who might be sterilized under the provisions of the law. This development shows that sterilization law in Georgia is now in accord with the jurisprudence of the rights revolution of the 1960s and 1970s